Management of Endometrial Hyperplasia: A Survey of Members of the Korean Gynecologic Oncology Group. Issue 7 (1st September 2015) - Kim, Mi Kyoung; Seong, Seok Ju; Kim, Jae-Weon; Bae, Duk-Soo; Jeon, Seob; Kwon, Sang-Hoon; Lee, Taek Sang
Abstract : Objectives: This study aimed to investigate the current management of endometrial hyperplasia (EH) in Korea. Materials and Methods: This was an electronic survey, which included 40 questions, that was distributed to the members of the Korean Gynecologic Oncology Group in 2014. Results: In total, 50 (69%) of 72 members responded to the survey. The oral progestogens were the most popular choices for managing EH without atypia (simple hyperplasia(SH), 64%; complex hyperplasia (CH), 52%). In the case of CH with atypia, most of the gynecologist respondents would perform hysterectomy (95.9%). For fertility preservation, the oral progestogens were the most popular choices (SH, 75.5%; CH, 56.3%), followed by the levonorgestrel-releasing intrauterine system (LNG-IUS). More than 70% of the respondents reported use of dilatation and curettage as a follow-up method. Conclusions: Our survey results show that most of Korean gynecologic oncologists still prefer oral progestogens for conservative management of EH, notwithstanding the many successful reports on the LNG-IUS. As a follow-up evaluation method, dilatation and curettage is mostly used. To identify the optimum therapy, a randomized controlled trial comparing the LNG-IUS with continuous oral progestogens is required. Furthermore, a large-scale prospective study to confirm the most reliable technique for follow-up evaluation is necessary.